Analysis of Electric Field and Current Density on XLPE Insulator - M. H. M. Sharif; N. A. M. Jamail; N. A. Othman; M. S. Kamarudin (International Journal of Electrical and Computer Engineering (IJECE), 2017)
Good condition and size of the insulator are important to ensure the excellent electric field and current density performance because of aging and degradation HVDC cable problem. At present, the existing insulator which is XLPE insulator that had been used does not meet the capabilities criteria of HVDC cable due to the problem in terms of the condition of the insulator which is the presence of a void in the insulator. A research had been made with Quickfield Software to calculate the electric field and current density in the XLPE insulator of HVDC cable. A void is created in the XLPE insulator by using Quickfield Software by varying diameter of void and distance of void from conductor. XLPE insulator is taken as main research object. The results show that largest diameter of void and nearest distance of void from conductor distorts highest electric field and lowest current density. Therefore, it is important to study both electric field and current density to ensure good capabilities and safety of HVDC cable.